2015
DOI: 10.1590/01000683rbcs20140388
|View full text |Cite
|
Sign up to set email alerts
|

Soil Aggregation, Organic Carbon Concentration, and Soil Bulk Density As Affected by Cover Crop Species in a No-Tillage System

Abstract: Soil aggregation and the distribution of total organic carbon (toc) may be affected by soil tillage and cover crops. the objective of this study was to determine the effects of crop rotation with cover crops on soil aggregation, toc concentration in the soil aggregate fractions, and soil bulk density under a no-tillage system (NtS) and conventional tillage system (ctS, one plowing and two disking). this was a three-year study with cover crop/rice/cover crop/rice rotations in the brazilian cerrado. A randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 29 publications
3
22
0
4
Order By: Relevance
“…Generally, a more rapid loss of SOC may occur from macroaggregates than from microaggregates (Eynard et al, 2005). The SOC change under agricultural management may owe to the aggregate stability index (Nascente et al, 2015). Thus, soil aggregated fractionation has been widely applied to evaluate the SOC stability under contrasting tillage systems.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a more rapid loss of SOC may occur from macroaggregates than from microaggregates (Eynard et al, 2005). The SOC change under agricultural management may owe to the aggregate stability index (Nascente et al, 2015). Thus, soil aggregated fractionation has been widely applied to evaluate the SOC stability under contrasting tillage systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, a change in soil humic quality is not detectable since no significant variation in the soil C/N ratio is observed (Table 2). Nascente, Yuncong & Costa (2015), found that SOM concentration was negatively correlated with ρb in the surface soil horizon (0-10 cm), which are thought to contribute to a higher concentration of SOM with a lower ρ b .…”
Section: Soil Physical Propertiesmentioning
confidence: 96%
“…Rice is a dietary staple for half of the world's population (BELLON et al, 2006;KUMAR;LADHA, 2011;CRUSCIOL;COBUCCI, 2013). In Brazil, rice is cultivated in two distinct ecosystems: (a) irrigated flood plain (IFP) and (b) uplands.…”
Section: Introductionmentioning
confidence: 99%
“…These cultivation practices may also decrease fertilizer requirements via nutrient release from cover crop straw (VERNETTI JÚNIOR; GOMES; SCHUCH, 2009;NASCENTE et al, 2014). Nascente and Crusciol (2015) reported that the use of cover crops contributed to the increase in soil organic matter content. Cover plants can also significantly affect soil N and improve the crop development environment (NASCENTE et al, 2016).…”
Section: Introductionmentioning
confidence: 99%